2010
DOI: 10.1021/jp103224s
|View full text |Cite
|
Sign up to set email alerts
|

PbTiO3Nanoparticles Embedded in a Liquid Crystalline Elastomer Matrix: Structural and Ordering Properties

Abstract: Ferroelectric PbTiO3 nanoparticles were synthesized to be used as inorganic components of new composite materials based on a liquid crystalline elastomer (LCE) matrix. The preparation and characterization of the composite materials, with a relatively high concentration of PbTiO3 nanoparticles, in the form of thin films is described. The composite films retain the thermomechanical response typical of standard LCEs and the nanoparticles are distributed in the film in anisotropic structures indicating the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 50 publications
2
39
1
Order By: Relevance
“…The transition temperature decrease may in some cases be dependent on the concentration of nanoparticles. In the case of PbTiO 3 nanoparticles, the same authors found that the nematic transition point dropped from 74 to 72 to 71 °C for samples containing 0%, 1 wt% and 5 wt% PbTiO 2 respectively [55]. The glass transition follows a similar trend: from −4 °C to −6 °C and −7.5 °C for 0%, 1 wt% and 5 wt% samples.…”
Section: Thermal Properties and Thermal Actuationmentioning
confidence: 80%
See 4 more Smart Citations
“…The transition temperature decrease may in some cases be dependent on the concentration of nanoparticles. In the case of PbTiO 3 nanoparticles, the same authors found that the nematic transition point dropped from 74 to 72 to 71 °C for samples containing 0%, 1 wt% and 5 wt% PbTiO 2 respectively [55]. The glass transition follows a similar trend: from −4 °C to −6 °C and −7.5 °C for 0%, 1 wt% and 5 wt% samples.…”
Section: Thermal Properties and Thermal Actuationmentioning
confidence: 80%
“…Perovskite-based ferroelectric PbTiO 3 nanoparticles have also been used to form composites with LCEs [55]. The PbTiO 3 nanoparticles were synthesized by sequential precipitation of TiCl 4 and Ph(NO 3 ) followed by calcination.…”
Section: Selection Of Nanoparticles and Lcesmentioning
confidence: 99%
See 3 more Smart Citations